The Relationship Between Self-Efficacy and Sexual Function in Patients with Type II Diabetes - Haddadi, Samira; Mirkohi, Mahdi Ghodrati; Akbari-Kamrani, Mahnaz (BALI MEDICAL JOURNAL, 2016)
Background: Diabetes is a common chronic disease that is increasingly observed in almost all countries of the world. The treatment and prevention of diabetes largely depend on patients’ self-efficacy in performing self-care behaviors. Accordingly, the present study was conducted to examine the relationship between self-efficacy and sexual performance in patients with type II diabetes. Methods: In the present correlational study, 200 patients with type II diabetes (based on physicians’ diagnosis) participated. Using convenience sampling method, the samples were selected out of the whole population of diabetic patients who referred to Shahid Bahonar and Rajaei Hospitals in the city of Karaj (Iran). The data were collected through a multi-faceted questionnaire covering demographic characteristics of the participants, the Diabetes Management Self-Efficacy Scale (DMSES), the Female Sexual Function Index (FSFI) and the Male Sexual Function Index (MSFI). Then, the collected data were analyzed through Pearson correlation test, multiple linear regression analysis, independent t-test and ANOVA. Results: The results showed a positive significant relationship between self-efficacy and sexual function (p<0.001); regression coefficient of the predictor variable ‘self-efficacy’ was 0.217 (p<0.017). Conclusion: Self-efficacy plays an important role in the lives of diabetic patients; it is also important in sexual performance of diabetic patients. Therefore, based on the results of this study, the significant relationship between self-efficacy and sexual function must be considered in the treatment of patients with type II diabetes.
Keywords: Type II Diabetes, Self-Efficacy, Sexual Function, Iranian Males and Iranian Females